2010
DOI: 10.1213/ane.0b013e3181cb3f8b
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 3% Hypertonic Saline and Mannitol for Brain Relaxation During Elective Supratentorial Brain Tumor Surgery

Abstract: Our results suggest that HTS provided better brain relaxation than did mannitol during elective supratentorial brain tumor surgery, whereas it did not affect ICU stays or hospital days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 28 publications
4
70
0
Order By: Relevance
“…In line with previous reports [9,35,39,40], our SR confirmed that the administration of HTS heightened the levels of serum sodium, which was sustained for 6 h, and promoted a temporary reduction of potassium [20-22, 24, 26]. In contrast, mannitol caused a transient acute dilutional hyponatremia [20,22,26], with a concomitant stepwise increase of potassium over time [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports [9,35,39,40], our SR confirmed that the administration of HTS heightened the levels of serum sodium, which was sustained for 6 h, and promoted a temporary reduction of potassium [20-22, 24, 26]. In contrast, mannitol caused a transient acute dilutional hyponatremia [20,22,26], with a concomitant stepwise increase of potassium over time [22].…”
Section: Discussionsupporting
confidence: 92%
“…While all hyperosmolar agents promote diuresis, HTS exerts a weaker diuretic effect than mannitol, possibly because it stimulates the release of antidiuretic hormones [9,39,40]. By contrast, mannitol infusion could induce hypovolaemia through an increase in diuresis [13,[20][21][22][23][24][25]28].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies have compared the effects of mannitol and HS on whole blood coagulation. Instead, the focus has been on what effect these two solutions have on ICP, hemodynamics, and acid base balance [8][9][10][11][12][13][14][15]. The results of these studies have been difficult to interpret, and only in one study the osmolarity and the volume have been the same for both solutions [8].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive use of HS can lead to hypernatremia [7]. Earlier studies suggest that HS is equally effective or even better than mannitol in reducing brain swelling in patients undergoing craniotomy [8][9][10][11][12][13][14][15]. However, due to variable study protocols, e.g., regarding osmolarity and administered volumes, definite conclusions about differences in physiological responses or occurrence of untoward effects cannot be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the preoperative peritumoral edema and intracranial pressure were not recorded, and only a single dose of mannitol (1 g/kg) was administered. Wu et al [10] compared the effects of 160 mL of 3% hypertonic saline and 150 mL of 20% mannitol on brain relaxation. Their study suggested that 3% hypertonic saline provided better relaxation; however, the lengths of hospital and intensive care unit stays did not significantly differ.…”
Section: Introductionmentioning
confidence: 99%